The Technology Parameters Optimization of Extracting Natural Cellulose Fibers from Eulaliopsis Binata - 曲丽君 郭肖青 由瑞华 孙亚宁 迟德玲 (Dong Hua da xue xue bao. Zi ran ke xue ban., 2010)
The extracting process and parameters optimization of Eulaliopsis binata fibers were studied.The components of Eulaliopsis binata were tested,the cellulose contents was about 45%,and the lignin content was as high as 18.5%.And the components of Eulaliopsis binata fibers were compared with some bast fibers.The analysis of physical and chemical properties related to acid,alkali,and auxiliary agent about cellulose and pectin,and lignin components in Eulaliopsis binata fibers were investigated.The chemical processing was employed to extract Eulaliopsis binata fibers in which NaOH as cooking agent and Na5P3O10 as auxiliary agent.The universal rotatable composite experiment design was used to get the highly precise regression equations,in which the NaOH concentration,the auxiliary agent Na5P3O10 concentration and the processing time were the main technological parameters.The residual gum content,fiber fineness,fiber strength,and fiber length of Eulaliopsis binata were the evaluation indexes.Based on the relation among parameters of extracting process,degumming effect and quality indexs of Eulaliopsis binata fibers,the optimum parameters of extracting process on Eulaliopsis binata fibers can be obtained.The fibers extracted from Eulaliopsis binata can be developed as one kind of natural cellulose fibers suitable for producing various textile products.